Three-pion Bose-Einstein correlations measured in proton-proton collisions - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2025)
A study on the Bose-Einstein correlations for triplets of same-sign pions is presented. The analysis is performed using proton-proton collisions at a centre-of-mass energy of $$ \sqrt{s} $$= 7 TeV, recorded by the LHCb experiment, corresponding to an integrated luminosity of 1.0 fb−1. For the first time, the results are interpreted in the core-halo model. The parameters of the model are determined in regions of charged-particle multiplicity. This measurement provides insight into the nature of hadronisation in terms of coherence, being consistent with the presence of coherent emission of pions.